The New Discovery Technology in Industry 4.0; the Role of Virtual Reality (VR) to Encourage Student’s Knowledge in History Education - Suroyo Suroyo; Bedriati Ibrahim; Yanuar Al-Fiqri; Bima Maulana Putra; M. Noval Dwi Pratama (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
In industry 4.0, the use of technology is increasing, especially in the field of education. The application of Virtual reality can be a modern technology-based teaching method, so that it can increase students' understanding of the history study program in learning local history in Pekanbaru. The research is a type of Research and Development, where the subject in this study is a student of the history study program at the University of Riau, with the object in the form of virtual reality based on local history. The analysis and evaluation of virtual reality uses observation and interview instruments, so that the results found are in the form of increased student understanding after using virtual reality in the classroom in local history learning.